Identification of crossbred buffalo genotypes and their chromosome segregation patterns - Harisah, M.; Azmi, T.I.; Hilmi, M.; Vidyadaran, M.K.; Bongso, T.A.; Nava, Z.M.; Momongan, V.; Basrur, P.K. (Canadian Science Publishing, 1989)
Chromosome analysis on different breed types of water buffaloes (Bubalus bubalis) was undertaken to identify their karyotypes and to determine the pattern of chromosome segregation in crossbred water buffaloes. Altogether, 75 purebred and 198 crossbred buffaloes including 118 from Malaysia and 80 from the Philippines, were analyzed in this study. The diploid chromosome number of the swamp buffalo from both countries was 48 and that of the river buffalo was 50, while all F1 hybrids exhibited 49 chromosomes. The F2 hybrids consisted of three different karyotype categories (2n = 48, 2n = 49, and 2n = 50), whereas the backcrosses included two different karyotype categories each, with 2n = 48 and 2n = 49 in the three quarters swamp types and 2n = 49 and 2n = 50 in the three quarters river types. Chi-square tests on pooled data from Malaysia and the Philippines indicated that the distribution of different karyotype categories of F2 animals did not deviate significantly from the 1:2:1 ratio expected if only balanced gametes with 24 and 25 chromosomes were produced by the F1 hybrids. In the three quarters swamp and three quarters river types, the respective karyotypic categories were in ratios approximating 1:1. The distribution of chromosome categories among the F2 hybrids and backcrosses suggests that only genetically balanced gametes of the F1 hybrids are capable of producing viable F2 and backcross generations.